OPTIMIZATION OF MANUAL FILLING MACHINE TO AUTOMATIC FILLING IN THE COSMETIC INDUSTRY - Fikry Adham Guna; Soemardiono, Soemardiono (Kohesi: Jurnal Sains dan Teknologi, 2024)
Machines are equipment that companies absolutely need in carrying out the production process. In the industrial world, automation systems are very important outside of manufacturing. Automation is the use of control systems and information technology to reduce human interaction in the production process of goods and services. An automation system also requires the role of an operator whose aim is to organize and run the system so that it can work well. In the development of automation systems, of course, this requires a general (universal) control device that does not require special power to operate, and can be applied to various types of equipment and is appropriate for its intended use. In this test, research data is collected from data obtained from speed testing from the PLC monitor program which is set directly to measure speed and filling so that it remains the same .